93.9k views
0 votes
Y = 10 - 2x
x = y - 4
How do you solve this system using substitution?

User Jonrsharpe
by
5.2k points

2 Answers

7 votes
Y=10-2(y-4) and you would get
Y=10-2y-4y
Y=10-(-2y)
Y=10+2y
Y=-10
Now plug -10 in
I’m pretty sure it’s right :)
User Peter Willemsen
by
5.0k points
5 votes

Answer:

im not sure what answer you are trying to find but i hope this helped

Explanation:

y = 10 - 2x

x = y - 4

(input x)

y = 10 - 2(y - 4)

y = 10 - 2y + 8

3y = 10 + 8

3y = 18

y = 6

User Nitsua
by
5.5k points